Walking backwards into the future: the need for a holistic evolutionary approach in Pacific health research - Elizabeth Matisoo-Smith; Anna L. Gosling (Taylor & Francis Group, 2018)
Context: The Pacific region has had a complex human history. It has been subject to multiple major human dispersal and colonisation events, including some of the earliest Out-of-Africa migrations, the so-called Austronesian expansion of people out of Island Southeast Asia, and the more recent arrival of Europeans. Despite models of island isolation, evidence suggests significant levels of interconnectedness that vary in direction and frequency over time. The Pacific Ocean covers a vast area and its islands provide an array of different physical environments with variable pathogen loads and subsistence opportunities. These diverse environments likely caused Pacific peoples to adapt (both genetically and culturally) in unique ways. Differences in genetic background, in combination with adaptation, likely affect their susceptibility to non-communicable diseases. Objectives: Here we provide an overview of some of the key issues in the natural and human history of the Pacific region which are likely to impact human health. We argue that understanding the evolutionary and cultural history of Pacific peoples is essential for the generation of testable hypotheses surrounding potential causes of elevated disease susceptibility among Pacific peoples.